Las tecnologías de la información y la comunicación (TIC) en educación secundaria: una revisión sistemática [Revisiones Sistemáticas de Literatura] - Peralta Roncal, Liliana Ethel (2024)
Information and communication technologies are digital tools capable of interconnecting people for different purposes. It is through them and a greater interactivity that new educational experiences have arisen to better adapt to the personal needs of each student. In this context, this study aims to analyze information related to the relevance of ICT use in learning within secondary education and during the last decade, through a systematic review of the literature under the PRISMA method. A total of 58 articles were compiled in the selection process. The review result indicated that ICTs are considered innovative tools within the educational field, and their significance has considerably grown as a result of the COVID-19 pandemic. However, there are still a few challenges to overcome to implement them efficiently, this step requiring hard work on the part of teachers and educational institutions themselves.